Efficacy and safety of hepatic artery infusion chemotherapy combined with tyrosine kinase inhibitors plus programmed death-1 inhibitors for hepatocellular carcinoma refractory to transarterial chemoembolization - Lin, Long-Wang; Ke, Kun; Yan, Le-Ye; Chen, Rong; Huang, Jing-Yao (Frontiers in Oncology, 2023)
Background The subsequent therapy for hepatocellular carcinoma (HCC) patients with refractory to transarterial chemoembolization (TACE) is still controversial. This study was performed to evaluate the efficacy and safety of combination therapy comprising hepatic artery infusion chemotherapy (HAIC), lenvatinib, and programmed death-1 inhibitors relative to HAIC combined with lenvatinib. Methods In this single-center retrospective study, we analyzed data from HCC patients with refractory to TACE from June 2017 to July 2022. Primary study outcomes were overall survival (OS) and progression-free survival (PFS), while the secondary outcomes were the objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events. Results We enrolled 149 patients finally, including 75 patients who received HAIC combined with lenvatinib plus PD-1 inhibitors therapy (HAIC+L+P group) and 74 patients who received HAIC combined with lenvatinib therapy (HAIC+L group). The median OS in the HAIC+L+P group (16.0; 95% CI: 13.6 18.3 months) was significantly higher compared to the HAIC+L group (9.0; 95% CI: 6.5 11.4 months) (p = 0.002), while the median PFS in the HAIC+L+P group (11.0; 95% CI: 8.6 13.3 months) was significantly higher compared to the HAIC+L group (6.0; 95% CI: 5.0 6.9 months) (p < 0.001). Significant between-group differences in DCR (p = 0.027) were found. Additionally, 48 pairs of patients were matched after propensity matching analysis. The survival prognosis between two groups before propensity matching is similar to that after propensity matching. Moreover, the percentage of patients with hypertension in the HAIC+L+P group was significantly higher compared to the HAIC+L group (28.00% vs. 13.51%; p = 0.029). Conclusions A combination therapy of HAIC, lenvatinib, and programmed death-1 inhibitors significantly improved oncologic response and prolonged survival duration, showing a better survival prognosis for HCC patients with refractory toTACE.